Tingkat Adopsi Inovasi Peternak dalam Beternak Ayam Broiler di Kecamatan Bajubang Kabupaten Batang Hari - Lestari, Widiya; Hadi, Syafril; Idris, Nahri (Jurnal Ilmiah Ilmu-Ilmu Peternakan, 2009)
The purpose of this research was to nknow the level of breeder innovation adoption in broiler chicken livestock and factors influencing innovation adoption in broiler chicken livestock in district Bajubang of Batang Hari regency. The research method was survey. Sample location was choosen by purposive sampling based on breeder broiler chicken. The respondent were choosen by sensus. Thurstone scale method was used to know the breeder innovation adaption level in broiler chicken livestock.Multiple linier regression analysis was used to know the factors influence innavation adoption level. The result shown that innovation adoption level in district Bajubang of Batang Hari regency is high level (89,62%). Multiple linier regression analysis shown that factor influencing innovation adoption levelwas breeder age. Factors not real influence was education level, family size, cattle farm exprience, the number of cattle and incomeÂ  The conclusion was innovation adoption level in broiler chicken livestock in district Bajubang of Batang Hari regency influenced by breeder age.